Land Policy in Resilience Building: The Case of the Evros River Basin in Northern Greece - Delladetsimas, Pavlos-Marinos; Katsigianni, Xenia (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2023)
Land policy as an all-encompassing socio-economic domain has experienced a long-standing evolutionary process operating either as a foundational component of spatial planning or as an inherent policy entity in developmental strategies. Either way has endowed the advancement of numerous policy tools of its own, like land administration-registration practices, land banks, land expropriation, land consolidation, pre-emption rights, air rights development transfer, development rights, taxation, re-parceling and land compensation mechanisms. At the same time, land policy has been a rather critical element in all phases of safety planning (emergency planning, recovery-reconstruction planning and disaster mitigation-prevention planning). This study elaborates on the issue of land policy as an eminent component interlinking spatial planning, safety planning and development policies. Further on it highlights the wide variety of land policy tools that allow dealing (proactively and reactively) with disaster management and promoting resilient territories. Set in this context, the aim of this article is to reveal the importance of land policy in flood protection, focusing on a distinct flood risk setting: the Evros River Basin in Northern Eastern Greece; and more specifically in the making of an integrated safety-resilience planning strategy.